2019
DOI: 10.2147/ott.s191239
|View full text |Cite
|
Sign up to set email alerts
|

<p>Fenofibrate potentiates chemosensitivity to human breast cancer cells by modulating apoptosis via AKT/NF-&kappa;B pathway</p>

Abstract: BackgroundCumulatively, evidences revealed that fenofibrate used in the therapy of hyperlipidemia and hypercholesterolemia has anti-cancer effect in multiple cancer types. However, its function and underlying mechanism of chemosensitization in breast cancer remain poorly understood.Materials and methodsThe cytotoxicity of fenofibrate and anti-cancer drugs in breast cancer cells was determined by MTT. Apoptosis and mitochondrial membrane potential were measured using flow cytometry. Caspases and PARP cleavage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Meanwhile, the study has indicated that the activation of caspase-9 and caspase-3 and the permeabilization of mitochondrial outer membrane affect fenofibrate-elevated chemosensitivity. Moreover, the synergistic effects of fenofibrate with paclitaxel, tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), ABT-737, and doxorubicin significantly augment chemosensitivity to enhance the apoptosis of breast cancer cells ( 72 ). Basing on the emerging evidence, fenofibrate is a promising candidate in breast cancer treatments.…”
Section: Ppar-α Modulators and Cancermentioning
confidence: 99%
“…Meanwhile, the study has indicated that the activation of caspase-9 and caspase-3 and the permeabilization of mitochondrial outer membrane affect fenofibrate-elevated chemosensitivity. Moreover, the synergistic effects of fenofibrate with paclitaxel, tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), ABT-737, and doxorubicin significantly augment chemosensitivity to enhance the apoptosis of breast cancer cells ( 72 ). Basing on the emerging evidence, fenofibrate is a promising candidate in breast cancer treatments.…”
Section: Ppar-α Modulators and Cancermentioning
confidence: 99%
“…Fenofibrate activates peroxisome proliferator-activated receptors α (PPARα), a transcription factor that stimulates the beta-oxidation of fatty acids ( Schoonjans et al, 1996 ). It has been found to reduce cellular proliferation and boost apoptosis in cancer cells ( Yamasaki et al, 2011 ; Sun et al, 2019 ). Since cholesterol-lowering drugs can modulate proliferation, migration, and invasion and inhibit tumorigenesis, this review article will discuss the effects of these drugs in correlation with Akt signaling.…”
Section: Cholesterol-lowering Drugsmentioning
confidence: 99%
“…Fenofibrate, a non-statin cholesterol lowering drug is used in the therapy of hyperlipidemia and hypercholesterolemia. It is reported to act on Akt/NF-κB pathway and reduce the phosphorylated Akt and NF-κB p65 in SKBR3 and MDA-MB-231 cells ( Sun et al, 2019 ). Akt/NF-κB pathway in breast cancer blocks the activity of pro-apoptotic genes such as Bok, Bax and BIM ( Bentires-Alj et al, 2001 ; Inta et al, 2006 ).…”
Section: Cholesterol-lowering Drugs On Akt Signalingmentioning
confidence: 99%
“…A literature review revealed that fenofibrate has anticancer effects in many malignancies, including pancreatic cancer [38], lung adenocarcinoma [39], hepatocellular carcinoma [40], melanoma [41], glioblastoma [42,43], oral cancer [44,45], prostate cancer [46,47], breast cancer [48], neuroblastoma [49], and angiosarcomas [50]. Fenofibrate also increases the sensitivity of esophageal carcinoma [51,52] and head and neck squamous cell carcinoma [37] to radiotherapy, and that of breast cancer to chemotherapy [36]. Exisulind is widely reported to have anticancer effects in a variety of malignancies, including non-small cell lung cancer [53], colon cancer [54][55][56][57][58], prostate cancer [59], breast cancer [60], head and neck squamous cell carcinoma [61], and pan-cancer [62].…”
Section: Discussionmentioning
confidence: 99%
“…NU1025 is involved in regulating the sensitivity of human cervical cancer HeLa cells to the triazoloacridone compound c-1305 through the p53 pathway, thereby synergistically participating in tumor inhibition 34 . Fenofibrate has anticancer effects in a variety of cancers 35 , and it increases the sensitivity of tumors to chemotherapy and radiotherapy 36 , 37 . A literature review revealed that fenofibrate has anticancer effects in many malignancies, including pancreatic cancer 38 , lung adenocarcinoma 39 , hepatocellular carcinoma 40 , melanoma 41 , glioblastoma 42 , 43 , oral cancer 44 , 45 , prostate cancer 46 , 47 , breast cancer 48 , neuroblastoma 49 , and angiosarcomas 50 .…”
Section: Discussionmentioning
confidence: 99%